K-ALJABAR - ISWATI, ISWATI; suryoto, Suryoto (MATEMATIKA, 2010)
K-algebra is an algebra structure built on a group so that characters of a group will apply also at K-algebra. If at group there is subgroup and homomorfism group, hence at K-algebra there is K-subalgebra and K-homomorfism. By using characters of group, will be proved characters applied at K-algebra. Â